Multiple extraction conditions to produce phytochemical- and antioxidant-rich Alternanthera sessilis (red) extracts that attenuate lipid accumulation in steatotic HepG2 cells - Yap, Cheng Hong; Junit, Sarni Mat; Aziz, Azlina Abdul; Kong, Kin Weng (Elsevier, 2019)
Alternanthera sessilis (red) is an edible herb used by Malaysians to alleviate hyperlipidaemia. This study aimed to produce phytochemical- and antioxidant-rich A. sessilis (red) whole plant extracts using multiple extraction conditions. The lipid-lowering effects of the extracts against steatosis in HepG2 cells were assessed. Ethanolic extracts (100%, 50 °C, 24 h) showed the highest total phenolic content (83.5 mg GAE/g extract) while water extracts (50 °C, 24 h) had the highest extraction yield (20.5%). Ethyl acetate extracts (50 °C, 24 h) showed the highest flavonoids (641 mg RE/g), triterpenoids (46.1 mg UAE/g) and betalains (amaranthin: 72.7 mg/g; betaxanthin: 74.5 mg/g; betanin: 73.1 mg/g). Despite this, the ethanolic extracts showed the highest antioxidant activities (DPPH IC50: 82.6 μg/ml; TEAC: 0.51 mmol TE/g; FRAP: 1.95 mmol Fe2+/g). UHPLC analyses showed the presence of 4 polyphenolic compounds from the extracts; trans-ferulic acid, rutin, quercetin and apigenin. Different concentrations (5–40 μg/ml) of ethanolic, ethyl acetate and water extracts produced at 50 °C, 24 h were selected for cell-based assays. Two assays were used to determine their preventive and ameliorative effects against palmitate-induced lipid accumulation in HepG2 cells. Results indicated that the ethanolic extracts were the most effective at preventing steatosis (intracellular lipid content reduced by 28.3%) while water extracts showed the highest decrease of steatosis (intracellular lipid content reduced by 30%). The results were comparable with the common drug fenofibrate (0.1 mM) for hyperlipidaemia, indicating the potential of this plant's extract to reduce hepatic lipid accumulation. © 2019 Elsevier Ltd